1973
DOI: 10.1172/jci107402
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Human Fibrinogen by Plasma α2-Macroglobulin-Enzyme Complexes

Abstract: A B S T R A C T This study demonstrates that human plasma a2-macroglobulin preparations possess an enzymic activity that degrades fibrinogen, resulting in the formation of products whose structure resembles that of circulating fibrinogen catabolites. The sequence of degradation is similar to that observed in plasmincatalyzed digests, in that Aa-chain fragmentation precedes that of B,8-chain. The addition of plasminogen activators to plasma induced an increase in the N-atosyl-L-arginine methyl ester HCl esteras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
1

Year Published

1974
1974
1988
1988

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(68 citation statements)
references
References 37 publications
(48 reference statements)
7
60
1
Order By: Relevance
“…The active site of the enzyme in the complex, however, retained the capacity to hydrolyze synthetic amino acid esters, and in the case of the a2-macroglobulin-plasmin complex, retained fibrinogenolytic activity (52). In the present investigation, derivatives were not identified after the interaction of Cis and C1 inactivator.…”
Section: Discussioncontrasting
confidence: 53%
“…The active site of the enzyme in the complex, however, retained the capacity to hydrolyze synthetic amino acid esters, and in the case of the a2-macroglobulin-plasmin complex, retained fibrinogenolytic activity (52). In the present investigation, derivatives were not identified after the interaction of Cis and C1 inactivator.…”
Section: Discussioncontrasting
confidence: 53%
“…However, kallikrein inhibitorx activity remained normal, and the decrease in prekallikrein did not correlate with the onset of shock. In gram-negative sepsis, decreased prekallikrein and kallikrein inhibitory activity (4,5) Unlike the kallikrein-Cl-INH complex, a plasma kallikrein-a2-macroglobulin complex might possess residual esterolytic and proteolytic activity like the plasmin-a2-macroglobulin complex (31). a2-Macroglobulin antigen did not increase in the febrile episode consistent with the observation that it is not an acute phase reactant (32) and the inhibitor is not elevated in typhoid fever (33).…”
Section: Methodssupporting
confidence: 64%
“…These studies showed that the 16-amino acid A peptide gave the same immunoreactivity with the two antisera, whereas Aa chain fragment 1-51, the NH2-terminal disulfide )lasmin digestion of the supernate of the 50% ethanol precipitate was found molecule all showed to give the lowest FPA values (Table IV). Such cona molar basis with centrations of ethanol (7.7% in the incubation mixture L2 antiserum.2 It was with antiserum) slightly inhibited binding in the assay fibrinogen (23) dur- (Table IV), and an equivalent amount of ethanol was might be responsible therefore included in the standard fibrinopeptide inhiients of the Aa chain bition curve. Tests of the dialysate of the ethanol prenmunoreactivity with cipitate of plasma showed that the high levels of imLim.…”
Section: Resultsmentioning
confidence: 96%